Evaluación de la competencia clínica de tutores de residentes de medicina familiar y comunitaria - Pedregal González, M. (Aten Primaria, 2004)
OBJECTIVES: We show the first experience of the application of an objetive and structured clinical evaluation (OSCE) procedure to family medicine trainers, that has been carried out in Andalucia. The objective is to use a competence evaluation instrument that, in the short term, will be used not only for trainer accreditation but also for other public sanitary professionals PARTICIPANTS: Tutors of family and commnity medicine residents DESIGN: Observational descriptive SETTING: Educational unity of family medicine PRINCIPAL MEASUREMENTS: The competencial components to be assessed are the following: anamnesis, physical exploration, communication, technical skill, management, family attention y preventive activities. The clinical situations were selected using the following priority criteria: prevalence, clinical gravity, prevention and early diagnosis importance, case complexity, doctor's capacity of evaluation and simplicity RESULTS: Thirteen family medicine trainers took part in the OSCE. Their average age was 42.8±3.6 years. The test had an overall reliability coefficient (Cronbach's alpha) of 0.73. The overall mean score of the participants was 73±6.2. The best results about the competencial components were family attention, communication and technical skill CONCLUSIONS: The OSCE can be a convenient tool for family medical trainer evaluation, helping to orientate their education in the weak points and, in the near future, it can also be used as an instrument do accredit family medicine trainers